Certification of Standard Reference Material 660c for powder diffraction. Issue 1 (March 2020) - Black, David R.; Mendenhall, Marcus H.; Brown, Craig M.; Henins, Albert; Filliben, James; Cline, James P.
Abstract : The National Institute of Standards and Technology (NIST) certifies a suite of Standard Reference Materials (SRMs) to evaluate specific aspects of instrument performance of both X-ray and neutron powder diffractometers. This report describes SRM 660c, the fourth generation of this powder diffraction SRM, which is used primarily for calibrating powder diffractometers with respect to line position and line shape for the determination of the instrument profile function (IPF). It is certified with respect to lattice parameter and consists of approximately 6 g of lanthanum hexaboride (LaB6 ) powder. So that this SRM would be applicable for the neutron diffraction community, the powder was prepared from an isotopically enriched 11 B precursor material. The microstructure of the LaB6 powder was engineered specifically to yield a crystallite size above that where size broadening is typically observed and to minimize the crystallographic defects that lead to strain broadening. A NIST-built diffractometer, incorporating many advanced design features, was used to certify the lattice parameter of the LaB6 powder. Both Type A, statistical, and Type B, systematic, uncertainties have been assigned to yield a certified value for the lattice parameter at 22.5 °C of a = 0.415 682 6 ± 0.000 008 nm (95% confidence).